2020
DOI: 10.1155/2020/4283027
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity among Adults with Low Socioeconomic Status Living in Industrialized Countries: A Meta-Ethnographic Approach to Understanding Socioecological Complexities

Abstract: Introduction. This article is a meta-ethnographic analysis of qualitative studies to explore complex social ecological aspects (individual, microsystem, mesosystem, exosystem, and macrosystem) of physical activity among socioeconomically disadvantaged groups living in industrialized countries. Method. Using MeSH keywords, we searched major electronic databases including Medline, EMBASE, CINAHL, and PsycINFO in order to identify relevant publications published between January 2000 and October 2018. We included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 66 publications
(152 reference statements)
3
27
0
Order By: Relevance
“…Studies in Bangladesh have reported that, despite the introduction of NCD corners in the country and implementation of NCD related services, the public sector role has been limited to providing NCDs and related services to combat the growing burden of NCDs [13,20,25]. However, developing a functional team and a service delivery system in a resource-poor setting like Bangladesh is possible and has been highlighted by several studies, but there is a need for translating these potentials to actions [28,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Bangladesh have reported that, despite the introduction of NCD corners in the country and implementation of NCD related services, the public sector role has been limited to providing NCDs and related services to combat the growing burden of NCDs [13,20,25]. However, developing a functional team and a service delivery system in a resource-poor setting like Bangladesh is possible and has been highlighted by several studies, but there is a need for translating these potentials to actions [28,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, psychostimulants can cause sleeplessness ( 37 ). Low socioeconomic status may also lead to social deterioration ( 38 ), lower physical activity level ( 39 ), and unbalanced diet ( 40 ).…”
Section: Negative Effects Of Decreased Quality Of Life and Psychoemotional And Socioeconomic Burden On Sleep Qualitymentioning
confidence: 99%
“…SEM acknowledges that an individual’s behaviour is shaped through multilevel factors. In general, five hierarchical levels of SEM have been recommended and used in social science, psychology and health science sectors: individual, interpersonal, community, organizational and policy levels ( Newes-Adeyi et al , 2000 ; Lounsbury and Mitchell, 2009 ; Rawal et al , 2020 ). Themes denoting factors influencing the practice of IPC to reduce HAIs were categorized under the various SEM levels, and other arising themes were also integrated ( Figure 1 ).…”
Section: Data Collection Toolsmentioning
confidence: 99%